2014
DOI: 10.1021/ef500095j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Macromolecular Structure Elements from a Green River Oil Shale, II. Characterization of Pyrolysis Products by 13C NMR, GC/MS, and FTIR

Abstract: This paper is Part II of a study of the chemical structural components of the organic matter of oil shale in the Green River formation. Three sections of a well-characterized oil shale core from the Utah Green River formation were demineralized, and the resulting kerogen was pyrolyzed at 10°C/min in nitrogen at atmospheric pressure at temperatures up to 525°C. The pyrolysis products (light gas, tar, and char) were analyzed using 13 C NMR, GC/MS, and (FTIR). Pyrolysis yields of 80% (daf basis) were achieved at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…These predictions did not compare well to the thermogravimetric analysis (TGA) data 3 or tar and total yield data obtained in a laboratory kerogen retort by Hillier et al 25 and Fletcher et al 18 The chemical structure of the kerogen in oil shale is much different from the chemical structure in coal; therefore, this result was not surprising. Rate coefficients were determined for a first-order distributed activation energy model (DAEM) of mass release using TGA pyrolysis data on the parent oil shales of the demineralized samples referenced in Table 1.…”
Section: ■ Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…These predictions did not compare well to the thermogravimetric analysis (TGA) data 3 or tar and total yield data obtained in a laboratory kerogen retort by Hillier et al 25 and Fletcher et al 18 The chemical structure of the kerogen in oil shale is much different from the chemical structure in coal; therefore, this result was not surprising. Rate coefficients were determined for a first-order distributed activation energy model (DAEM) of mass release using TGA pyrolysis data on the parent oil shales of the demineralized samples referenced in Table 1.…”
Section: ■ Resultsmentioning
confidence: 69%
“…The molecular weight of the light gas (MW lg ) was set to an average of 20 amu, and the molecular weight of the heavy gas (MW hg ) was then calculated from the combined gas molecular weight (calculated from the NMR parameters by the CPD model 10 (1) where y lg = g 2 /(g 1 + g 2 ) and y hg = g 1 /(g 1 + g 2 ), and y lg and y hg were set to 0.2 and 0.8, respectively. The bridge reaction rate coefficients were then adjusted slightly to obtain best fit with the kerogen retort data of Fletcher et al 18 The new rate coefficients are shown in Table 3.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest known deposit is the Eocene Green River Formation in Western Colorado, Eastern Utah, and Southern Wyoming [Dyni, 2003;Johnson et al, 2009]. Kerogen, which constitutes most of oil shale's organic matter, is a highly cross-linked, macromolecular material distributed in a heterogeneous inorganic matrix [Fletcher et al, 2014;Solum et al, 2013]. Pyrolysis of oil shale breaks down the complex kerogen network structure to produce shale oil and natural gas [Hillier et al, 2013;Sun et al, 2014].…”
Section: Introductionmentioning
confidence: 99%